Clinical Condition and Comorbidity of Patients with Emergency Hemodialysis at Dr. Soetomo General Academic Hospital, Indonesia in January 2023 - Viola Awriendina; Aditiawardana; Budi Utomo (Journal of Comprehensive Science, 2026)
Emergency hemodialysis (HD) can happen because of numerous factors such as delayed referral to the nephrologist doctor and inadequate care of patient comorbidities. It was challenging because this procedure had a higher mortality than planned hemodialysis. This study aims to present the characteristics of patients who underwent emergency hemodialysis. An observational description exploration was applied in this retrospective cross-sectional study of all patients receiving emergency hemodialysis at Dr. Soetomo General Academic Hospital in January 2023. The inclusion criteria of having complete evidence data in medical reports indicate the patient’s need for this therapy. We collected data on the patient's age, gender, type of renal failure, HD status, comorbidities, and indications of hemodialysis procedure. A univariate analysis performed for this study. A total of 104 patients undergoing emergency hemodialysis were evaluated in this study. The majority of patients were male (50.96%), in the age of 40-59 range (50%), from Surabaya (51%), and had CKD V (88.46%). The most potential causes of declined kidney function were hypertension (65.38%) and diabetes mellitus (37.5%). This study also examined most indications for emergency hemodialysis: hypervolemia (75.96%) and uremia syndrome (68.26%) with 89.42% patient with multiple indications. The study population was dominated by CKD V patients who had previously undergone regular HD and several patients underwent emergency hemodialysis more than once in January 2023. The majority of patients are in the productive age range and have hypertension and diabetes mellitus. This study also found that hypervolemia and uremic syndrome are the most common indications for emergency hemodialysis.